Disability Human Rights Law - Anna Arstein-Kerslake (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Disability Human Rights Law is an emerging field. It is an amalgamation of human rights law, disability studies, and disability rights law. It views rights in a novel way, opening a new line of scholarly inquiry. It sees rights as they apply to the individual, with regard to the individual$1 (Bs particular abilities, needs, and circumstances. Disability Human Rights Law represents a shift in the field of human rights. The traditional, and often archaic, rights boundaries are broken down. Civil and political rights exist entwined with social, economic, and cultural rights. The rights of the community and the rights of the individual are not always distinguishable and are often dependent upon one another. The Convention on the Rights of Persons with Disabilities (CRPD) is the epitome of this shift and the epicenter of a new wave of rights protection. This book focuses on this new field. The aim of the book is to begin to explore the potential of Disability Human Rights Law to transform modern human rights law.s
English
Keywords: Disability; Legal Capacity; Accessibility; Human Rights; Convention on the Rights of Persons with Disabilities; Access to Justice